Desire thinking and craving as predictors of problematic Internet pornography use in women and men. (January 2023) - Marino, Claudia; Melodia, Fiordalisa; Pivetta, Erika; Mansueto, Giovanni; Palmieri, Sara; Caselli, Gabriele; Canale, Natale; Vieno, Alessio; Conti, Francesca; Spada, Marcantonio M.
Highlights: Desire thinking and craving play a role in problematic cyberpornography use. Imaginal prefiguration is associated to craving and in turn to verbal perseveration. Verbal perseveration is associated to problematic cyberpornography use for men. The model holds overall comparably for women and men. Women score lower than men on all the main variables of the study. Abstract: Introduction: According to the recent adaptation of the I-PACE model, desire thinking and craving might be closely related to problematic Internet pornography use. The overall aim of the present study was to investigate the role of two components of desire thinking (imaginal prefiguration and verbal perseveration) and craving in problematic Internet pornography use. Furthermore, we examined gender differences in the underlying mechanism linking desire thinking to problematic Internet pornography use. Method: A total of 414 Italian adults (mean age = 27.55 years, SD = 6.13; age range = 18–58; 53.6 % men) participated in this study. Participants completed an online survey to assess problematic Internet pornography use, pornography craving, desire thinking and problematic Internet use. Path analyses and a multi-group approach were used to test the relationships among variables and to explore gender differences. Results: Imaginal prefiguration was associated to pornography craving which, in turn, was associated to verbal perseveration as proximal antecedent of problematic Internet pornography use, above and beyond the effect of age, relationship status, and problematic Internet use. Two paths significantly differed between men and women: the path between verbal perseveration and problematic Internet pornography, which for women was weaker and did not reach significance; and the path between problematic Internet use and problematic Internet pornography use that was not significant for women. Conclusions: In line with the I-PACE model, the present study provided support for the potential role of desire thinking in problematic Internet pornography use as a specific Internet-use disorder and expanded the literature in the field by testing unexplored gender differences. Preventive and clinical implications are discussed.